Safety and efficiency of crossing Y-stent-assisted coiling with LEO stents in treatment of wide-necked intracranial bifurcation aneurysms - WANG Kaishan; CHEN Yujie; ANG Jun (陆军军医大学学报, 2023)
Objective To explore the safety and efficiency of crossing Y-stent-assisted coiling with LEO stents in treatment of wide-necked intracranial bifurcation aneurysms. Methods The clinical data and follow-up images of 336 patients with wide-necked intracranial bifurcation aneurysms admitted to the neurosurgery department of the First Affiliated Hospital of Army Medical University from 2018 to 2022 were collected and analyzed retrospectively.Among them, 55 patients received crossing Y-stent-assisted coiling with LEO stents.The success rate of aneurysm treatment, operation-related complications, incidences of perioperative ischemic and hemorrhagic complications were observed.Raymond classification were conducted on cerebral angiographs immediately after operation and at the end of follow-up to evaluate the efficiency of embolization.Modified Rankin Scale (mRS) was used to evaluate the neurological function of the patients at discharge and during clinical follow-up.Computed tomography angiography (CTA) and magnetic resonance angiography (MRA) were performed to evaluate the recurrence rate during postoperative follow-up. Results Successful embolization was performed in the 55 patients with LEO stent-based crossing Y-shaped stenting, and no adverse events such as poor stent opening or stent folding were observed.Intraoperative stent thrombosis occurred in 1 case (1.82%), delayed ischemia in 2 cases (3.64%), and no perioperative bleeding events was observed.Immediate postoperative angiography showed dense embolism (Raymond class Ⅰ) in 50 cases (90.91%), residual tumor neck (Raymond class Ⅱ) in 3 cases (5.45%), and Raymond class Ⅲ in 2 cases (3.64%).The imaging results of 40 patients during a follow-up from 6 months to 2 years postoperatively revealed that 38 cases (95%) were at Raymond Class Ⅰ and 2 cases (5%) at Raymond Class Ⅱ.For the 9 patients undergoing CTA or MRA re-examination, no recurrence was observed.The imaging results during postoperative follow-up indicated that efficiency improvement was achieved in all cases when compared to the conditions immediately after operation.At discharge, 50 cases had a mRS score of 0~1, 1 case of 2, 1 case of 3, 2 cases of 4, and 1 case of 5.The mRS scores were obviously improved in a follow-up period from 4 to 24 months, with 52 cases having a score of 0~1, 1 case of 2, 1 case of 3, 1 case of 4, and 1 case of 6. Conclusion Crossing Y-stent-assisted coiling with LEO stents has advantages of high success rate and safety, low recurrence rate and incidence of perioperative ischemic events, and sound short-term efficacy in treatment of wide-necked intracranial bifurcation aneurysms.But further observation is needed for long-term efficacy.